Peer selection and influence effects on adolescent alcohol use: a stochastic actor-based model - Mundt Marlon P; Mercken Liesbeth; Zakletskaia Larissa (BMC, 2012)
Abstract Background Early adolescent alcohol use is a major public health challenge. Without clear guidance on the causal pathways between peers and alcohol use, adolescent alcohol interventions may be incomplete. The objective of this study is to disentangle selection and influence effects associated with the dynamic interplay of adolescent friendships and alcohol use. Methods The study analyzes data from Add Health, a longitudinal survey of seventh through eleventh grade U.S. students enrolled between 1995 and 1996. A stochastic actor-based model is used to model the co-evolution of alcohol use and friendship connections. Results Selection effects play a significant role in the creation of peer clusters with similar alcohol use. Friendship nominations between two students who shared the same alcohol use frequency were 3.60 (95% CI: 2.01-9.62) times more likely than between otherwise identical students with differing alcohol use frequency. The model controlled for alternative pathways to friendship nomination including reciprocity, transitivity, and similarities in age, gender, and race/ethnicity. The simulation model did not support a significant friends' influence effect on alcohol behavior. Conclusions The findings suggest that peer selection plays a major role in alcohol use behavior among adolescent friends. Our simulation results would lend themselves to adolescent alcohol abuse interventions that leverage adolescent social network characteristics.